Negotiating Belief and Tradition: A Study of Saparan Ritual in the Multireligious Community of Selo - Zulkarnain, Ahmad; Najib, Luqman; Arief N. R, Achmad Dicky (Sekretariat Badan Moderasi Beragama dan Pengembangan Sumber Daya Manusia (BMBPSDM) Kementerian Agama RI, 2025)
This research aims to understand mystical synthetics in Selo through a case study of the Saparan tradition. This tradition reflects the cultural expression and gratitude of the Javanese people, who try to achieve harmony with supernatural powers. The variety of religions that Selo residents embrace does not conflict with Javanese beliefs but melts into the Saparan tradition. This research uses an anthropological approach and Ricklefs' mystical systemic ideational principle. The method used is field research with primary sources from informants in Selo hamlet and secondary data from various references. The results of this study show that the Saparan tradition is divided into two sessions: preparation and celebration. The celebration session is further categorized into three types: communal, individual, and entertainment. The dialectic between religious and Javanese beliefs does not cause conflict but results in a merging. Javanese mythology remains firmly upheld by the Selo community because it is believed to play a direct role in their lives. The Saparan tradition is carried out as a form of gratitude, prayer to ancestral spirits, and an effort to maintain harmony with supernatural forces.